2022
DOI: 10.1007/s00405-022-07685-0
|View full text |Cite
|
Sign up to set email alerts
|

Flexible endoscopic evaluation of swallowing in children with type 1 spinal muscular atrophy

Abstract: Purpose This study aimed to report on implementing flexible endoscopic evaluation of swallowing (FEES) in infants and toddlers with type 1 spinal muscular atrophy (SMA). In addition, a comparison of FEES results and clinical scores was carried out. Methods A prospective pilot study was conducted including ten symptomatic children with SMA type 1 (two SMN2 copies). They started treatment with one of the three currently approved therapies for SMA at a median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…21 A recent case series reported the use of FEES as an alternative method of evaluation in this population. 15 This study showed the presence of post swallow residue in all but one patient. Residue ranged from trace to severe in the vallecula and pyriform sinus (pharyngeal residue), regardless of the trialed consistency.…”
Section: Patient Characteristicsmentioning
confidence: 50%
See 4 more Smart Citations
“…21 A recent case series reported the use of FEES as an alternative method of evaluation in this population. 15 This study showed the presence of post swallow residue in all but one patient. Residue ranged from trace to severe in the vallecula and pyriform sinus (pharyngeal residue), regardless of the trialed consistency.…”
Section: Patient Characteristicsmentioning
confidence: 50%
“…Given the limited number of patients, it is difficult to draw conclusions about the short-and long-term impact of this finding. 15 FEES composes the benefit of avoiding radiation exposure and provides detailed information regarding secretion management, in addition to aspiration and presence of pharyngeal residue. A limitation of the use of FEES is that it does not provide comprehensive evaluation of the oral phase of swallowing, which as demonstrated in this data set can often be abnormal in treated children.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations